Asset maintenance in Australian commercial buildings - West, Jye; Evangelista, Ana; Siddhpura, Milind; Haddad, Assed (Frontiers in Built Environment, 2024)
Introduction: This study examines the complex link between regular maintenance procedures and the effectiveness of business-related assets in Australia. Commercial buildings are essential to the country's economy, and the variables affecting their worth must be carefully analysed. Methods: This study evaluates the relationship between asset value and maintenance frequency, examines how maintenance practices affect building performance, and considers industry perspectives on improperly versus correctly maintained assets. Results: The study's findings highlight the significance of renovations, along with adaptive reuse, in raising asset value; however, despite various maintenance techniques available, the Australian commercial building industry has challenges. Budgetary constraints, for instance, pose a significant hurdle, with many companies struggling to allocate sufficient funds for comprehensive maintenance plans. The findings of this research highlight the positive shift towards technology-driven maintenance procedures in business establishments in Australia. The adoption of computerised Maintenance Management Systems (CMMS) and Building Management Systems (BMS) is rising, automating repetitive tasks, improving maintenance procedures, and enabling data-driven decisions. Discussion: This study thoroughly explains the complex processes influencing the value and usefulness of commercial architecture resources in the Australian setting by addressing the differing perspectives within the real estate industry. Future research on this topic should focus on recognising the psychological components of decision-making concerning maintenance practices. Investigating how psychological prejudices, perceptions of danger, and organisational culture affect the choices made by property owners, facility administration, and others can help us better understand why some maintenance methods are preferred over others.